Assessing escalator pedestrian traffic dynamics amid COVID-19 pandemic using hybrid simulation. (26th August 2021) - Mykoniatis, Konstantinos; Angelopoulou, Anastasia; Smith, Tianqi Gao
Pedestrian behaviour in urban spaces has abruptly changed amidst the COVID-19 pandemic due to government-issued restrictions such as social distancing. It is unclear whether pedestrian behaviour will remain altered and/or urban spaces will be changed accordingly post-pandemic. Taking these changes and uncertainties, as well as the unique characteristics of pedestrian traffic as opposed to vehicle traffic, into consideration, this study creates a hybrid simulation model using the AnyLogic simulation software. The simulation model can be used to examine the efficiency of several types of escalator pedestrian behaviours in non-crowded scenarios, such as emergent/evacuation vs. regular operation, capacity and number of available escalators, escalator's dimensions (e.g., height and length) and speed, and pedestrian preference (e.g., standing vs. walking). This generic simulation model allows future users to evaluate the efficiency of the escalator operation scenarios they would like to simulate by providing output measures such as time spent in system and throughput and allowing customisations of escalator dimensions and pedestrian-related parameters based on user-specific requirements.